The Making of Salty Soy Sauce From Koro Benguk (Mucuna pruriens) (Study of Saline Concentration of Salt Solution and Duration of Maromi's Fermentation) - Arie Febrianto Mulyadi; Wignyanto .; Eka Yaniar Putri Nur Hidayah (UPT Penerbitan Universitas Jember, 2014)
The objectives of this study were to determine the saline concentration and moromi’s fermentation duration of koro benguk salty soy sauce at best organolepticly and determine consumers’ preferences towards koro benguk salty soy sauce from the best treatment results. The study was conducted using a randomized design method using two factors: the saline concentration (17%; 20%; and 23%) and duration of moromi’s fermentation (2; 3; and 4 weeks). The best treatment results based on the Friedman test was on the saline concentration of 17% and moromi’s fermentation duration was 4 weeks, with the NP value of 1,000; had a preference color level of 5:40 (liked); aroma of 4.30 (rather liked); flavor of 4.55 (rather liked); and viscosityof 5.05 (liked). The obtained protein was 7.14%; and dissolved solids of 27 brix. Consumers’ preferences towards the best treatment showed that product of koro benguk salty soy sauce was acceptable to consumers. Keywords: Moromi’s Fermentation, Soy Sauce, Saline Concentration, Koro Benguk